2022
DOI: 10.3390/app12052668
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Photonic Generation of a Microwave Waveforms Scheme Based on a Dual-Polarization Dual-Drive Mach-Zehnder Modulator

Abstract: In this paper, a simple scheme for the generation of sawtooth, triangular, and square waveforms using an integrated dual-polarization dual-drive Mach-Zehnder modulator (Dpol-DDMZM) is proposed. By properly setting the working point and the modulation index of the Dpol-DDMZM, the desired microwave waveforms are easily obtained after photodetection. The proposed scheme for the photonic generation of microwave waveforms is analyzed both by simulation and experiment. The periodical sawtooth, triangular, and square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The DSB optical mm-wave system has two primary obstacles: the occurrence of fading and the temporal displacement of codes, which is mainly caused by chromatic dispersion of the fiber [10]. It has been shown that OCS and SSB optical mm-waves are resistant to fading, but their propagation distance is restricted by the length of time shift of the codes [11,12]. Some researchers [13] proposed a technique that efficiently prohibits the manipulation of codes that generate optical mm-wave signals with a quadrupling frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The DSB optical mm-wave system has two primary obstacles: the occurrence of fading and the temporal displacement of codes, which is mainly caused by chromatic dispersion of the fiber [10]. It has been shown that OCS and SSB optical mm-waves are resistant to fading, but their propagation distance is restricted by the length of time shift of the codes [11,12]. Some researchers [13] proposed a technique that efficiently prohibits the manipulation of codes that generate optical mm-wave signals with a quadrupling frequency.…”
Section: Introductionmentioning
confidence: 99%